2016
DOI: 10.1136/heartjnl-2015-308993
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activity and concerns in people with coronary heart disease from a population-based study

Abstract: Objective Sexual activity is a central component of intimate relationships, but sexual function may be impaired by coronary heart disease (CHD). There have been few representative population-based comparisons of sexual behaviour and concerns in people with and without CHD. We therefore investigated these issues in a large nationally representative sample of older people. Methods We analysed cross-sectional data from 2979 men and 3711 women aged 50 and older from the Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 28 publications
2
24
0
3
Order By: Relevance
“…28 A recent longitudinal study found no association between the use of β blockers and erectile dysfunction. 28 It is safe to prescribe phosphodiesterase type 5 inhibitors (such as sildenafil, vardenafil, and tadalafil) in patients with erectile dysfunction who have stable disease after myocardial infarction.…”
Section: Sexual Activitymentioning
confidence: 97%
See 1 more Smart Citation
“…28 A recent longitudinal study found no association between the use of β blockers and erectile dysfunction. 28 It is safe to prescribe phosphodiesterase type 5 inhibitors (such as sildenafil, vardenafil, and tadalafil) in patients with erectile dysfunction who have stable disease after myocardial infarction.…”
Section: Sexual Activitymentioning
confidence: 97%
“…28 A recent longitudinal study found no association between the use of β blockers and erectile dysfunction. 28 It is safe to prescribe phosphodiesterase type 5 inhibitors (such as sildenafil, vardenafil, and tadalafil) in patients with erectile dysfunction who have stable disease after myocardial infarction. 27 A US guideline recommends that nitrate medications should be avoided within 24 hours of taking sildenafil or vardenafil and within 48 hours of taking tadalafil based on a small randomised trial.…”
Section: Sexual Activitymentioning
confidence: 97%
“…CAD deeply affects sexual function in both men and women (34,35), while sex is the basis of intimate relationships. Reduced sexual activity and satisfaction, erection problems, and orgasmic problems have been described in these patients (36).…”
Section: Discussionmentioning
confidence: 99%
“…In their Heart publication, Steptoe et al 9 report an elegant study whereby cross-sectional data from 2979 men and 3711 women aged 50 and older from the English Longitudinal Study of Ageing are presented. Sexual behaviour with a partner spouse (of either gender: 93.6% of men and 94.7% of women, heterosexual only) and their concerns were assessed by a validated self-completion questionnaire, and analyses were weighted for non-response with covariates including comorbidities, age and drugs.…”
Section: Statinsmentioning
confidence: 99%
“…Steptoe et al 9 have excluded patients who did not have CHD (defined as a doctor diagnosis of MI or angina pectoris) but had a history of stroke or heart failure. The natural history of these conditions and a possible different aetiology may justify their exclusion.…”
Section: Role Of Agementioning
confidence: 99%